ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENGGAJIAN KARYAWAN (STUDI KASUS : PT. KOSAMBI LAKSANA MANDIRI) - K, Oktaviani; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2017)
Payroll system for companies mostly have used computer technology or computer-based information systems, but there are still some companies that do not implement them as well as on PT. Kosambi Laksana Mandiri. In this company in the payroll system is still using manual calculation and use the auxiliary program MS. Excel. The goal in this study Analyze and study the problems of employee payroll information system at PT. Kosambi Laksana Mandiri and produce a prototype system of employee payroll information on PT. Kosambi Laksana Mandiri. System design in this study using a UML (Unified Modelling Language) that use case diagrams, activity diagrams and class diagrams. Meanwhile, in the manufacture of a prototype system using MySQL tools for designing the database and Adobe Dreamweaver CS5 to design a prototype system. In this study generates payroll information system prototype PT. Like a Kosambi Mandiri to manage computerized payroll data, perform calculations salary every month automatically and presents reports required salary every month or every year.